Spent Hen Protein Hydrolysate with Good Gastrointestinal Stability and Permeability in Caco-2 Cells Shows Antihypertensive Activity in SHR - Hongbing Fan; Wenlin Yu; Wang Liao; Jianping Wu (Foods, 2020)
Spent hens are a major byproduct of the egg industry but are rich in muscle proteins that can be enzymatically transformed into bioactive peptides. The present study aimed to develop a spent hen muscle protein hydrolysate (SPH) with antihypertensive activity. Spent hen muscle proteins were hydrolyzed by nine enzymes, either individually or in combination; 18 SPHs were assessed initially for their in vitro angiotensin-converting enzyme (ACE) inhibitory activity, and three SPHs, prepared by Protex 26L (SPH-26L), pepsin (SPH-P), and thermoase (SPH-T), showed promising activity and peptide yield. These three hydrolysates were further assessed for their angiotensin-converting enzyme 2 (ACE2) upregulating, antioxidant, and anti-inflammatory activities; only SPH-T upregulated ACE2 expression, while all three SPHs showed antioxidant and anti-inflammatory activities. During simulated gastrointestinal digestion, ACE2 upregulating, ACE inhibitory and antioxidant activities of SPH-T were not affected, but those of SPH-26L and SPH-P were reduced. ACE inhibitory activity of gastrointestinal-digested SPH-T was not affected after the permeability study in Caco-2 cells, while ACE2 upregulating, antioxidant and anti-inflammatory activities were improved; nine novel peptides with five–eight amino acid residues were identified from the Caco-2 permeate. Among these three hydrolysates, only SPH-T reduced blood pressure significantly when given orally at a daily dose of 1000 mg/kg body weight to spontaneously hypertensive rats. SPH-T can be developed into a promising functional food ingredient against hypertension, contributing to a more sustainable utilization for spent hens while generating extra revenue for the egg industry.